Experimental installation for wear tests of materials and coatings - Stechyshyn, M.; Dykha, O.; Oleksandrenko, V.; Tsepenyuk, M.; Kurskoi, V.; Oleksandrenko, Ye. (Problems of Tribology, 2024)
On the basis of the analysis of existing tribological testing methodologies, which includes the selection of controlled wear parameters, the influence of the type of friction, contact geometry, surface roughness, the scheme of tribological research, the choice of a machine 2168UМТ for friction testing of materials is substantiated. The friction machine allows you to install three samples at the same time, change the pressure in the contact zone in a wide range, control the moment of friction, the rotation frequency of the counterbody, the number of revolutions (friction path), change the rotation frequency, respectively, the sliding speed, automatically limit the distance traveled and other functions. The method of wear is adopted according to the finger-ring scheme, linear wear is monitored using an indicator rack with a value of divisions of the measuring device of 0.001 mm. To fix the samples on the machine caliper, holders were designed and manufactured, which ensure the self-fixation of the sample on the counterbody - a spherical joint made of the rolling body of the bearing. due to the fact that the samples were pressed against the counterbody with a force corresponding to the nominal contact pressure, they were self-aligned. After the sample was self-assembled, the whole structure was fixed by tightening the nuts. The counterbody is made of a rolling bearing ring, the material is steel SHX15, the hardness of the base is HRC 61. Three devices are mounted on the caliper for permanent lubrication of the running track immediately before the approaching sample. Thus, at certain values of pressure and speed, the mode of marginal friction can be reached, which was marked by a low coefficient of friction.